The Role of Team Synergy in Infection Control: A Systematic Review of Healthcare Collaboration - Asiri, Yahya Ali Yahya; Asiri , Ahmed Amer Ali; Asiri, Ahmed Amer Mohammed; Alqahtani, Ahmed Jarallah; Alahamari, Abdullah Mohammed Saeed; Asiri, Abdulrahman Ayidh Nasser; Al ahmari, Saad Moshabab Audah; Alnami, Mohammed Hassan Ahmad; Alnmai, Abdullah Hassan Ahmad; Alasiri, Ali Mohammed Saeed (Journal of Ecohumanism, 2024)
Background: Infection control is a critical component of patient safety in healthcare settings, requiring coordinated efforts among medical staff. Effective collaboration and synergy among healthcare professionals, including physicians, nurses, infection control specialists, and support staff, are essential to reducing healthcare-associated infections (HAIs). However, barriers such as hierarchical structures, lack of communication, and inadequate training often hinder teamwork, impacting infection prevention outcomes. Objective: This systematic review aims to analyze the role of team synergy and interdisciplinary collaboration in improving infection control practices within healthcare institutions. The study identifies key factors that enhance or hinder effective teamwork in infection prevention and explores evidence-based strategies for fostering collaboration. Methods: A comprehensive literature search was conducted across databases including PubMed, Scopus, Web of Science, and Cochrane Library. Studies published between 2016 and 2024 focusing on teamwork, interdisciplinary collaboration, and infection control in healthcare settings were included. The review follows the PRISMA guidelines for systematic reviews, with data extracted on study design, intervention strategies, and impact on infection control outcomes. Results: The findings indicate that structured teamwork interventions, such as shared decision-making, cross-disciplinary training, and standardized communication protocols, significantly reduce infection rates. Hospitals with well-defined team roles and interprofessional coordination demonstrate higher compliance with infection prevention protocols. However, challenges such as resistance to collaborative change and lack of institutional support remain obstacles to effective teamwork in infection control. Conclusion: Healthcare institutions must prioritize fostering a culture of teamwork and synergy among medical staff to enhance infection control measures. Implementing structured teamwork training, leadership engagement, and communication strategies can improve patient safety and reduce HAIs. Future research should explore innovative technologies, such as AI-driven collaboration tools, to optimize infection control strategies